Iron-based metal–organic frameworks and derivatives for electrochemical energy storage and conversion - Adegoke, Kayode Adesina; Oyebamiji, Abel Kolawole; Adeola, Adedapo O.; Olabintan, Abdullahi Biodun; Oyedotun, Kabir O.; Mamba, Bhekie B.; Bello, Olugbenga Solomon (Coordination chemistry reviews, 2024)
•Fe-MOF nanomaterials are efficient electrocatalysts for energy storage and conversion.•Recent advances in synthesis strategies and applications of Fe-MOFs were highlighted.•Overview of MOF materials, structural diversity and design of Fe-MOF were highlighted.•DFT calculations have prospect for detail understanding and mechanistic information of these materials.•Challenges and the corresponding promising strategies for improving the efficiency of Fe-MOF materials were presented. Renewable energy remainsa prominent research hotspotbecause of its potential to reduce the globalreliance on fossil fuels, which isexperiencing a significant decline. Additionally, it has become highly importantto address the pressing issue of greenhouse gas emissions in order to meet the rising demandsin population growth,industrial activities, increasingglobal climate change, and energy consumption. Iron-based metal–organic frameworks (Fe-MOFs) are currently progressive intelligent materials with multipurpose and adjustable properties for clean energy applications due to their arrays of intrinsic physicochemical and structural characteristics. Despite increasing growth designs and fabrication of Fe-MOFs and their derived materials for a wide range of electrocatalytic energy applications, there is currently no review that demonstrates these recent developments of the same for energy storage and conversion systems, thereby creating knowledge gaps in this field. This study presents recent developments in electrocatalytic applications of Fe-MOF nanomaterials for energy storage (covering batteries and supercapacitors), oxygen and hydrogen productions, alcohol oxidation, nitrogen reduction reaction (NRR), CO2 reduction reaction (CO2RR) under different categories of Fe-MOF nanomaterials involving the pristine MOF, Fe-MOF-based electrocatalyst materials, MOF-derived electrocatalyst materials, and Fe-MOF composite materials. Brief fundamental concepts covering overview of MOF materials, structural diversity and design of Fe-MOF-based constituents were highlighted before the new development in the field.This work also demonstrates the amazing advantages that MOF materials have over conventional electrocatalysts, as well as the superiority of Fe-MOF-materials over their pristine equivalents. The paucity of computational and new technological information in this subject inspired the need to evaluate the prospect of density functional theory (DFT) calculations for a detailed understanding and mechanistic study of these materials for future advancements. Lastly, we discussed some challenges and the corresponding promising strategies for improving the efficiency of Fe-MOF materials to achieve viable industrial feasibility for energy storage and conversion applications. The review serves as a wake-up call to the scientific community on the need to design and fabricate new Fe-MOFs for lasting solutions to the shortage of clean energy.